Characterization of protein N-glycosylation by tandem mass spectrometry using complementary fragmentation techniques - Ford, Kristina; Zeng, Wei; Heazlewood, Joshua L.; Bacic, Anthony (Frontiers in Plant Science, 2015)
The analysis of post-translational modifications by proteomics is regarded as a technically challenging undertaking. While in recent years approaches to examine and quantify protein phosphorylation have greatly improved, the analysis of many protein modifications, such as glycosylation, are still regarded as problematic. Limitations in the standard proteomics workflow that can significantly prevent the identification of glycopeptides are the use of suboptimal peptide fragmentation methods. The development of modern tandem mass spectrometers has resulted in the availability of a variety of fragmentation options, many of which are becoming standard features on these instruments. We have used three common fragmentation techniques, namely CID, HCD and ETD, to analyse a plant glycopeptide and highlight how an integrated fragmentation approach can be used to characterize the N-glycan sites of